The effect of essential oils and calcified marine algae as natural alternatives to ionophore antibiotics on performance of feedlot cattle - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2014)
Dissertation (MSc Agric)--University of Pretoria, 2013.